2015
DOI: 10.1016/j.ejmech.2015.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, biological evaluation and molecular modeling studies of the PPARβ/δ antagonist CC618

Abstract: Herein, we describe the synthesis, biological evaluation and molecular docking of the selective PPARβ/δ antagonist (4-methyl-2-(4-(trifluoromethyl)phenyl)-N-(2-(5-(trifluoromethyl)-pyridin-2-ylsulfonyl)ethyl)thiazole-5-carboxamide)), CC618. Results from in vitro luciferase reporter gene assays against the three known human PPAR subtypes revealed that CC618 selectively antagonizes agonist-induced PPARβ/δ activity with an IC50 = 10.0 μM. As observed by LC-MS/MS analysis of tryptic digests, the treatment of PPARβ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 39 publications
(44 reference statements)
0
14
0
Order By: Relevance
“…It was proposed that heterogeneity in PPARβ/δ expression in cell types during tumorigenesis and the existence of natural PPARβ/δ agonists/antagonists and inverse agonists render the analysis of PPARβ/δ in cancer complex and controversial [66]. On the other hand, PPARβ/δ antagonism and inverse agonism have begun to attract attention, such as covalent antagonists GSK3787 and CC618 that were reported in studies on psoriasis and breast cancer, but the role in the liver is still unknown [67,68].…”
Section: Lessons From Liver-specific Ppard-null Micementioning
confidence: 99%
“…It was proposed that heterogeneity in PPARβ/δ expression in cell types during tumorigenesis and the existence of natural PPARβ/δ agonists/antagonists and inverse agonists render the analysis of PPARβ/δ in cancer complex and controversial [66]. On the other hand, PPARβ/δ antagonism and inverse agonism have begun to attract attention, such as covalent antagonists GSK3787 and CC618 that were reported in studies on psoriasis and breast cancer, but the role in the liver is still unknown [67,68].…”
Section: Lessons From Liver-specific Ppard-null Micementioning
confidence: 99%
“…The cysteine that is conserved across all three PPARs (hPPARα: Cys276, hPPARβ/δ: Cys249, and hPPARγ2(γ1): Cys313(285)) is located behind H3 and points into the narrow neck between the Ω pocket and the AF-2 pocket ( Figure 2) [1,70]. While this cysteine is demonstrably nucleophilic in PPARβ/δ [71][72][73][74][75] and PPARγ [66,67,71,[76][77][78][79][80][81][82][83][84], the eventual nucleophilicity of the corresponding Cys276 in PPARα appears to be surpassed by its neighbour Cys275 [76], which is located on the side of H3 that faces the Ω pocket. On the solvent-exposed side of H3, PPARα and PPARβ/δ contain additional cysteines (Cys278 and Cys251, respectively), the reactivities of which have not been established ( Figure 2).…”
Section: Ppar Structurementioning
confidence: 99%
“…While these ligands differed in their selectivity for PPARβ/δ versus the other PPAR subtypes and in their rate of reaction with Cys249 [74], treatment of PPARβ/δ with either of these ligands resulted in the formation of a Cys249 5-trifluoromethyl-2-pyridyl thioether [75]. Although the aryl moiety appended to PPARβ/δ Cys249 is less bulky than the moieties appended to PPARγ Cys313 by treatment with GW9662, T0070907, or SB1404, this modification still inhibited activation of PPARβ/δ by classical agonists whose head groups bind to the AF-2 pocket, such as GW501516 or GW0742 ( Figure S4) [72][73][74]252]. Treatment of PPARβ/δ with CC618 or GSK3787 alone did not induce transcription in reporter gene assays [72,252] nor did treatment with GSK3787 cause the recruitment of the coactivator MED1 (TRAP220) in a TR-FRET-based assay [252].…”
Section: Ppar Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…(4‐methyl‐2‐(4‐(trifluoromethyl)phenyl)‐N‐(2‐(5‐(trifluoromethyl)‐pyridin‐2‐ylsulfonyl)ethyl)thiazole‐5‐carboxamide)) CC618 (Figure ) was a combinatorial compound of arylthiazole moiety of selective PPARδ agonist GW501516 with the 5‐trifluoromethyl‐2‐pyridylsulfone moiety of antagonist GSK3787 . In vitro luciferase reporter gene assays against the three known human PPAR subtypes revealed that CC618 selectively antagonized the GW501516‐induced (Figure ) PPARδ activity with an IC 50 of 10.0 μ m , while the IC 50 of GSK3787 was 5.0 μ m .…”
Section: Pparδ Antagonistsmentioning
confidence: 99%